2015
DOI: 10.1186/s12889-015-2529-0
|View full text |Cite
|
Sign up to set email alerts
|

Osteoarthritis prevalence and modifiable factors: a population study

Abstract: BackgroundThis study’s objectives were to investigate the prevalence of self-reported knee and hip osteoarthritis (OA) stratified by age and sex and to examine the association of modifiable factors with knee and hip OA prevalence. The study was conducted using randomly sampled data gathered from four communities in the province of Alberta, Canada.MethodsA large adult population sample (N = 4733) of individuals ≥18 years were selected. Health-related information was collected through telephone interviews and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
102
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(119 citation statements)
references
References 39 publications
11
102
0
6
Order By: Relevance
“…27 Obesity is related with these changes by means of two interconnected pathways: increased load caused by excessive weight, and systemic effects related with chronic inflammation linked to imbalance in the release of active peptides produced by the fat tissue known as adipocytokines. 22,28,29 The assessment of knee-related symptoms using KOOS score in this study has shown impact mainly regarding pain and other symptoms compared with the mean values in non-obese individuals as reported in a systematic review by Collins et al 30 In a prospective study, Edwards et al 31 observed significant improvement in the five domains of KOOS following weight loss, while Gudbergsen et al 32 reported improvement in pain and function in daily living domains after weight loss. Thus, the results observed in our study regarding the KOOS methodology were similar to those previously observed in the literature.…”
Section: Discussionmentioning
confidence: 57%
“…27 Obesity is related with these changes by means of two interconnected pathways: increased load caused by excessive weight, and systemic effects related with chronic inflammation linked to imbalance in the release of active peptides produced by the fat tissue known as adipocytokines. 22,28,29 The assessment of knee-related symptoms using KOOS score in this study has shown impact mainly regarding pain and other symptoms compared with the mean values in non-obese individuals as reported in a systematic review by Collins et al 30 In a prospective study, Edwards et al 31 observed significant improvement in the five domains of KOOS following weight loss, while Gudbergsen et al 32 reported improvement in pain and function in daily living domains after weight loss. Thus, the results observed in our study regarding the KOOS methodology were similar to those previously observed in the literature.…”
Section: Discussionmentioning
confidence: 57%
“…The Framingham Osteoarthritis Study estimated that the prevalence of radiographic and symptomatic hip OA was 19.6 and 4.2 %, respectively [4]. In Canada, the prevalence of selfreported OA was 14.8 % with 10.5 % on the knee and 8.5 % on the hip [5]. In Asia, the prevalence of symptomatic knee OA was 4.4 and 5.7 % in men and 19.2 and 10.3 % in women in Korea and China, respectively [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…For example, with one study with 4733 subjects in Alberta, Canada, the prevalence of knee OA is 6.3% for males and 8.9% for females, while the prevalence of hip OA is 4.4% for males and 7.6% for females [12]. This discovery suggests presence of sex difference in OA prevalence and incidence, with females generally at a higher risk.…”
Section: Gender and Oamentioning
confidence: 99%